Accounting for Australia’s threatened species: Estimating historical and recent change in terrestrial habitat - Katherine M. Giljohann; Karel Mokany; Simon Ferrier; Thomas D. Harwood; Chris Ware; Kristen J. Williams (Ecological Indicators)
Habitat retention and restoration are fundamental to minimising species extinctions. Mitigating impacts on threatened species habitat requires knowing where and how much habitat remains, the quality of the habitat, and how it is changing over time. A systematic approach is therefore essential for regular and consistent measurement of threatened species habitat that can be applied across multiple scales.We present a new approach to track progress in providing habitat for threatened species over time and space, and apply it to the Australian continent. This involves: 1) estimating the historical (pre-intensification) habitat distribution for listed threatened species, and 2) deriving a metric of habitat provision for threatened species by combining the historical habitat distributions with remotely sensed annual ecosystem condition data. We demonstrate the method for Australia using 1,518 nationally-listed threatened species and ecosystem condition data for 2017 and 2018, and present summaries by sub-national jurisdictions.Across Australia, intensively developed regions had the greatest number of threatened species based on estimated historical habitat. Between 2017 and 2018 threatened species habitat decreased in six of eight sub-national jurisdictions. Percent losses were greatest in the smallest jurisdictions, which were also estimated to retain the least threatened species habitat. As of 2018, less than 50 % of the historical habitat for threatened species is estimated to have remained across Australia. Improving ecosystem condition could have the largest benefits where multiple threatened species potentially co-occur or where little historical habitat remains.Our approach facilitates high-level assessments of status and trends in habitat provision to support threatened species. The data and metric are spatially explicit and scalable, enabling aggregation over any spatial area such as for biophysical ecosystem accounting. We provide the estimated historical habitat distributions to facilitate ongoing assessments.